Recovery from cortical blindness with mepivacaïne - Cohen, Laurent; Ponchel, Amélie; Kas, Aurélie; Ströer, Sébastian; Del Cul, Antoine; Guérineau de Lamérie, Guillaume; El Hachem, Randa; Crépin, Piirika; Morin, Alexandre (Annals of clinical and translational neurology, 2019)
We report the case of a patient suffering from cortical blindness following bilateral occipital stroke, who recovered normal vision in his right visual field following injection of the local anesthetic mepivacaïne. The effect was transient but reproducible, allowing the patient to lead a normal life. Effect duration increased after adjunction of paroxetine. We provide anatomical and functional brain imaging correlates of this improvement, showing particularly how functional connectivity is restored between intact perilesional cortex and distant brain regions. This serendipitous finding may potentially benefit patients suffering from visual but also nonvisual handicap following brain lesions.